Implications of Net Stable Funding Ratio (NSFR) on Islamic Bank Margins and Earning Management Practices: A Systematic Literature Review - Yuniorita Indah Handayani; Muhaimin Dimyati; Hayatul Maspufah; Nurshadrina Kartika Sari (ABM: International Journal of Administration, Business and Management, 2025)
The implementation of the Basel III Net Stable Funding Ratio (NSFR), although aimed at improving financial stability, has the potential to reduce Islamic bank margins and encourage profit management practices due to funding structure mismatches. This study aims to analyze and synthesize the literature on the implications of NSFR on margins and profit management practices in Islamic banking. Using the Systematic Literature Review (SLR) method based on PRISMA 2020 (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) for articles published between 2020 and 2025, the data were analyzed through narrative synthesis. The synthesis results show that NSFR causally suppresses profit margins through increased funding costs. Based on agency theory, this pressure on profitability creates a strong incentive for managers to engage in earnings management as a strategic response. This study formulates a conceptual framework that integrates liquidity regulations, financial performance, and managerial behavior.